PARANEOPLASTIC OPTIC NEUROPATHY AS AN INITIAL CLINICAL MANIFESTATION OF SMALL CELL LUNG CANCER. A CASE REPORT - Akbulut, E; Bayraktar, H; Tugcu, B (Ceska a slovenska oftalmologie, 2021)
Paraneoplastic optic neuropathy (PON) is a very rare condition. In this study, a case of PON whose first complaint was painless vision loss in one eye is presented. In the follow-up of our case, optic neuropathy developed in the fellow eye. Electromyography examination performed due to diffuse body pain and motor loss in the left extremity is compatible with peripheral sensorimotor polyneuropathy. Lung biopsy was planned due to EMG result and and lymphadenopathy detection in thorax computed tomography (CT). The biopsy result of the patient was reported as nonspecific hyperplasia. As the patient's complaints increased, the paraneoplastic antibody panel was requested and CV2 / CRMP5 antibody was found positive. Thereupon, as a result of repeated biopsy, our patient was diagnosed with small cell lung cancer. We think that paraneoplastic optic neuropathy should be considered in the differential diagnosis in patients with advanced age, smoking, painless subacute vision loss, optic disc swelling, and we should insist on research in this direction as in our case.
Keywords: Small cell lung cancer; Optic Nerve; Optic Nerve Diseases; nádory plic; nemoci zrakového nervu; Humans; Small Cell Lung Carcinoma; CV2/CRMP5 antibodies; malobuněčný karcinom plic; Papilledema; Lung Neoplasms; paraneoplastic optic neuropathy; nervus opticus; lidé; městnavá papila